Air and Seawater Quality Assessment Around Selected Area in Panjang Port Lampung Region - Salim, Agus; Ningsih, Nunung Isnaini Dwi; Sulaiman, Albertus (Proceeding International Conference on Science and Engineering, 2020)
The port area is a diverse business district, both industry and other activities. Even though it is positioned far from residential areas, the impact of its activities indirectly still reaches the surrounding community. The environmental conditions of the port area need to be controlled routinely so that their management does not violate applicable regulations. Environmental management is needed so that risks arising from all activities can be controlled. Panjang Port as one of the well-developed fuel storage terminals as part of the Pelindo II region. This study has been designed to assess air quality and seawater quality around Panjang Port, Bandar Lampung, Indonesia. Several air quality parameters and marine water quality parameters were monitored from 2011 to 2013. The air quality sampling conducted in the fuel storage tank area and chemicals as well as supporting facilities. The air quality parameters are SO2, NO2, O3, CO, H2S, and dust. The results of data analysis showed several air quality parameters such as SO2, NO2, O3, dust, H2S, and NH3 are below the threshold of minimum quality standard. Only the CO parameter tends to increase semester to semester. The seawater quality parameters include physical, chemical, and biological quality. Almost the physical quality parameters are below the quality standard, thus the chemical quality too, except the pH and TSS tends to higher than a quality standard. In general, these studies on air quality and seawater quality at the Panjang Port have been carried out well and the results show that the environmental conditions for the Panjang Port area are still quite good, only it is recommended to add a green area around the site.